2023
DOI: 10.3233/jifs-222232
|View full text |Cite
|
Sign up to set email alerts
|

Decision support for technology transfer using fuzzy quality function deployment and a fuzzy inference system

Abstract: Technology transfer plays an essential role in developing an organization’s capabilities to perform better in the market. Several protocols are defined for technology transfer. One of the main techniques in technology transfer is licensing, which significantly impacts profit and income. This study intends to develop a decision framework that integrates both a Fuzzy Inference System (FIS) and a two steps Fuzzy Quality Function Deployment (F-QFD) to assist an organization in selecting a licensor. To illustrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Thus, in work [3] it is indicated that the viability of technologies depends on innovativeness, cost, compatibility, safety, and environmental suitability. Effective support and management, including regular updates, is key.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thus, in work [3] it is indicated that the viability of technologies depends on innovativeness, cost, compatibility, safety, and environmental suitability. Effective support and management, including regular updates, is key.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%